Micropolar Fluid Model for Blood Flow through a Small Tapered Tube - Rajendra Kumar Tripathi, (AG Volumes, 2022)
The steady flow of blood through a small rigid circular tube with small tapering angles of 10 and 20 is analysed by a micro-continuum approach using the boundary conditions proposed by Ariman et al. [J Appl. Mech. (March 1974),1]. Analytical expression for flow velocity, micro-rotational velocity, volume flow rate and shear stress at blood vessel wall are obtained. The influence of hematocrit, Reynolds number and tapered angles on the flow characteristics are discussed. As the tapered angle increases the wall shearing stress increases resulting in a decrease in the velocity.